2018
DOI: 10.1016/s0140-6736(18)31380-1
|View full text |Cite
|
Sign up to set email alerts
|

Dressings and securements for the prevention of peripheral intravenous catheter failure in adults (SAVE): a pragmatic, randomised controlled, superiority trial

Abstract: Australian National Health and Medical Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
154
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(170 citation statements)
references
References 29 publications
(33 reference statements)
6
154
1
9
Order By: Relevance
“…The appropriateness guide does not address the choice between PVCs and midline catheters. The median dwell times for PVCs have been reported at 2‐6 days . Hence, the advantages in selecting midline catheters with an approximate mean dwell time of 14 days before premature removal seem obvious, despite their increased price.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriateness guide does not address the choice between PVCs and midline catheters. The median dwell times for PVCs have been reported at 2‐6 days . Hence, the advantages in selecting midline catheters with an approximate mean dwell time of 14 days before premature removal seem obvious, despite their increased price.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous therapy is an integral part of most hospital admissions. The majority of patients receive a peripheral venous catheter (PVC), as this catheter type is easily inserted and has a low complication rate . However, its use is seriously hampered by as short median dwell time of only 2‐6 days with considerable variation.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral venous catheter failure refers to various complications that necessitate PIVC removal caused by issues related to PVC insertion or management, such as dislodgement, phlebitis, infiltration, occlusion and infection (Marsh et al, ; Rickard et al, ). Chinese guidelines recommend regularly changing PVCs every 72 ~ 96 hr to reduce the risk of PIVC failure, and Swedish guidelines recommend regularly changing PVCs every 72 hr, with the exception of children and patients with difficult access (Vårdhandboken, ).…”
Section: Introductionmentioning
confidence: 99%
“…According to INS, transparent dressings should not be relied upon to act as the single source of securement indicating the lack of supportive evidence (Gorski et al 2016). Results of the study by Rickard et al (2018) demonstrated similar dislodgement outcomes (7-10%) for transparent dressings, bordered transparent, adhesive sutureless securement, and transparent and tissue adhesive with transparent dressing (Rickard et al 2018). While the tissue adhesive and transparent dressing had the lowest dislodgement (7%), the results were not statistically significant.…”
Section: Transparent Dressingsmentioning
confidence: 99%